Correction: Amido Ca(ii) complexes supported by Schiff base ligands for catalytic cross-dehydrogenative coupling of amines with silanes. Issue 17 (11th April 2019) - Forosenko, Natalia V.; Basalov, Ivan V.; Cherkasov, Anton V.; Fukin, Georgy K.; Shubina, Elena S.; Trifonov, Alexander A.
Abstract : Correction for 'Amido Ca(ii ) complexes supported by Schiff base ligands for catalytic cross-dehydrogenative coupling of amines with silanes' by Natalia V. Forosenko et al., Dalton Trans., 2018, 47, 12570–12581.